Base-flow segmentation and character analysis of the Huangfuchuan Basin in the middle reaches of the Yellow River, China - Zhang, Yaru; He, Yi; Mu, Xingmin; Jia, Liping; Li, Yanlin (Frontiers in Environmental Science, 2022)
In recent years, with the deterioration of the ecological environment, runoff in the Yellow River has been decreasing. Given these phenomena, it is necessary to research the base-flow segmentation methods and its characteristics. The Huangfuchuan Basin in the middle reaches of the Yellow River basin was selected as the research area. This paper calculated the base-flow with commonly used base-flow segmentation methods, including Base-flow index method (BFI), Hydrograph-separation techniques (HYSEP), and the digital filtering methods, and compared the applicability of these methods in the study area. Then the variation characteristics, abrupt change year, periodic change, and future trend of the base-flow were analyzed. The results are as follows: 1) Through the analysis and comparison of several common base-flow segmentation methods, these methods had a marked difference in base-flow segmentation. The variance and extreme-ratio of DF4 in the digital filtering methods were small. The correlation between DF4 and other methods was high. DF4 in the digital filtering methods was the most appropriate method in the research area. 2)The runoff and base-flow index presented a decreasing trend. The annual average runoff was 1,100.27 × 104 m3, and the maximum base-flow was 0.21. The base-flow also showed a significant decrease trend by the Mann-Kendall trend test, the average base-flow was 10,578.35 × 104 m3. 3) The base-flow had periodic variations of 3–6, 7–18, and 19–32. In the 19–32 years time scale, three oscillations alternated between abundant and dry. The whole time was 31 years as the center of the periodic change, the first primary cycle of base-flow change. 4) The base-flow mutation occurred in 1986. The Hurst index of base-flow in the Huangfuchuan Basin was 0.84. It was shown that the trend of future development is positively correlated with past change, showing a trend of continuous decrease. Selecting the appropriate method of base-flow segmentation and reasonably analyzing the variation characteristics of base-flow can provide scientific guidance for the ecological environment construction and water resource evaluation in the Huangfuchuan Basin and even the Yellow River Basin.